Review of bacterial cellulose production using agricultural and agroindustrial wastes: Physical and mechanical properties - Rincón, Alejandro; Restrepo, Gloria; Hoyos Velasco, Fredy Edimer (International Journal of Agricultural and Biological Engineering, 2025)
Bacterial cellulose (BC) is a biopolymer whose properties make it suitable for applications in medicine, pharmaceutics, food, environment, engineering, and chemistry. BC produced from agricultural/industrial material exhibits a wide variety of morphological, physical, and mechanical properties. BC production and yield are dependent on the agricultural material used, the content of nitrogen and phosphorus, the bacterial strain, and culture conditions. In this review, BC production is addressed, focusing on the effect of culture conditions and culture medium on the morphological, physical, and mechanical properties of BC, considering low-cost substrates as culture medium. The main contributions over closely related reviews are: 1) A compilation of BC production data, along with corresponding crystallinity and mechanical or physical properties, is provided to highlight the relationship between crystallinity and these properties within each study; 2) The different culture conditions of each cited study, as well as the blank or control treatment, are included in the data compilation to allow comparison of the effects of the culture conditions within each study; 3) The relationship between microstructure and physical and mechanical properties within each study is discussed; cases of simultaneous achievement of high BC production and either crystallinity or tensile strength are identified. From the data comparison, it follows that the BC production is similar to or better than that for standard Hestrin and Schramm (HS) medium in some studies, and its corresponding crystallinity or mechanical/physical properties are different. Then, a high BC production/yield does not guarantee improvement of crystallinity or physical/mechanical properties. In some cases, the crystallinity index is not significantly modified, but the corresponding physical/mechanical properties are. This implies that considering the physical/mechanical properties corresponding to the BC production/yield data is convenient in experimental studies on BC production using low-cost culture medium.Keywords: bacterial cellulose (BC), biomaterials, agricultural waste, nanocellulose, Gluconacetobacter, KomagataeibacterDOI: 10.25165/j.ijabe.20251805.9466Citation: Rincón A, Restrepo G M, Hoyos F E. Review of bacterial cellulose production using agricultural and agroindustrial wastes: Physical and mechanical properties. Int J Agric & Biol Eng, 2025; 18(5): 15–25.